2017
DOI: 10.1002/acm2.12038
|View full text |Cite
|
Sign up to set email alerts
|

Photon Optimizer (PO) prevails over Progressive Resolution Optimizer (PRO) for VMAT planning with or without knowledge‐based solution

Abstract: The enhanced dosimetric performance of knowledge‐based volumetric modulated arc therapy (VMAT) planning might be jointly contributed by the patient‐specific optimization objectives, as estimated by the RapidPlan model, and by the potentially improved Photon Optimizer (PO) algorithm than the previous Progressive Resolution Optimizer (PRO) engine. As PO is mandatory for RapidPlan estimation but optional for conventional manual planning, appreciating the two optimizers may provide practical guidelines for the alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…In the present work, the clinical plans (for CL-1 models) were generated with the PRO optimization engine and the AAA algorithm, while in the whole RP validation and subsequent model, the PO optimization and Acuros dose calculation algorithms were used. It is known that PO was found to prevail over PRO for VMAT planning [30, 31], and Acuros is more accurate than AAA [32, 33]. Concerning the optimizer, outperforming PO with respect to PRO, could have a double effect.…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, the clinical plans (for CL-1 models) were generated with the PRO optimization engine and the AAA algorithm, while in the whole RP validation and subsequent model, the PO optimization and Acuros dose calculation algorithms were used. It is known that PO was found to prevail over PRO for VMAT planning [30, 31], and Acuros is more accurate than AAA [32, 33]. Concerning the optimizer, outperforming PO with respect to PRO, could have a double effect.…”
Section: Discussionmentioning
confidence: 99%
“…A few investigators have reported the dosimetric differences in PO algorithm for IMRT/VMAT planning in a digital phantom, conventional prostate, head and neck, and brain treatments, knowledge‐based planning to rectal cancer patients and a single‐lesion lung SBRT and stereotactic brain treatments . For instance, Jiang et al evaluated the performance of PO over PRO for VMAT planning of 30 rectal cancer patients with or without knowledge‐based planning. A knowledge‐based model was generated using manually optimized PRO plans.…”
Section: Discussionmentioning
confidence: 99%
“…Fixed voxel resolutions of 1.25, 2.5 or 5 mm can be used during multiresolution optimization. For a single‐lesion treatment, a few investigators have reported dosimetric differences between PO and PRO optimization for IMRT/VMAT plans . For instance, the advantages and limitations of PO algorithm compared to its predecessor PRO for IMRT plans were evaluated by Binny et al Eleven plans including prostate, brain, and head and neck treatments were optimized using both PO and PRO algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…A published RapidPlan model for pre-surgical rectal cancer patients was used in this study[11,12,13]. As a brief review, the model was trained with 81 historical plans that were contoured and planned following Li's study [14].…”
Section: Methodsmentioning
confidence: 99%
“…Considering the large target volumes were relatively deep-seated, all historical plans were optimized with 10 MV flattened photon beams (10X) by experts. The robustness of the model has been validated on over 100 cases [1113].…”
Section: Methodsmentioning
confidence: 99%